Extending the theory of planned behavior to identify students’ investment intentions in internet money market funds - Baihui, Zhan; Bahador, Ku Maisurah Ku; Saat, Rafeah Mat (Edelweiss Applied Science and Technology, 2024)
This study investigates students’ investment intentions in Internet Money Market Funds (IMMFs) in the Chinese context by extending the Theory of Planned Behavior (TPB) to include factors or dimensions such as functional value, efficiency value, emotional value and social value. A quantitative research approach was used, taking data from a sample of university students in China. The results revealed that attitude, subjective norms, perceived behavioral control, and perceived value significantly influence students’ investment intentions in IMMFs. In addition, perceived value, including functional value, efficiency value, emotional value and social value, also positively affects investment intentions among university students, emphasizing the importance of students’ perceptions of usefulness, ease of use, emotional satisfaction and social benefits derived from investing. in IMMFs. These findings contribute to the advancement of theory and practical applications in the internet investment domain, especially in the context of the investment market in China.